Cerium-activated sol–gel silica glasses for radiation dosimetry in harsh environment. (1st April 2016) - El Hamzaoui, Hicham; Capoen, Bruno; Helou, Nissrine Al; Bouwmans, Géraud; Ouerdane, Youcef; Boukenter, Aziz; Girard, Sylvain; Marcandella, Claude; Duhamel, Olivier; Chadeyron, Geneviève; Mahiou, Rachid; Bouazaoui, Mohamed
Abstract: Cerium-doped silica glass has been prepared for ionizing radiation dosimetry applications, using the sol–gel route and densification under different atmospheres. In comparison with the glass densified under air atmosphere, the one obtained after sintering the xerogel under helium gas presents improved optical properties, with an enhancement of the photoluminescence quantum yield up to 33%, which is attributed to a higher Ce 3+ ions concentration. Such a glassy rod has been jacketed in a quartz tube and then drawn at high temperature to a cane, which has been used as active material in a fibered remote x-ray radiation dosimeter. The sample exhibited a reversible linear radioluminescence intensity response versus the dose rate up to 30 Gy s −1 . These results confirm the potentialities of this material for in vivo or high rate dose remote dosimetry measurements.